Macrolide-Peptide Conjugates as Probes of the Path of Travel of the Nascent Peptides through the Ribosome - Washington, Arren Z. (ACS Chem Biol, 2014)
[Image: see text] Despite decades of research on the bacterial ribosome, the ribosomal exit tunnel is still poorly understood. Although it has been suggested that the exit tunnel is simply a convenient route of egress for the nascent chain, specific protein sequences serve to slow the rate of translation, suggesting some degree of interaction between the nascent peptide chain and the exit tunnel. To understand how the ribosome interacts with nascent peptide sequences, we synthesized and characterized a novel class of probe molecules. These peptide–macrolide (or “peptolide”) conjugates were designed to present unique peptide sequences to the exit tunnel. Biochemical and X-ray structural analyses of the interactions between these probes and the ribosome reveal interesting insights about the exit tunnel. Using translation inhibition and RNA structure probing assays, we find the exit tunnel has a relaxed preference for the directionality (N → C or C → N orientation) of the nascent peptides. Moreover, the X-ray crystal structure of one peptolide derived from a positively charged, reverse Nuclear Localization Sequence peptide, bound to the 70S bacterial ribosome, reveals that the macrolide ring of the peptolide binds in the same position as other macrolides. However, the peptide tail folds over the macrolide ring, oriented toward the peptidyl transferase center and interacting in a novel manner with 23S rRNA residue C2442 and His69 of ribosomal protein L4. These data suggest that these peptolides are viable probes for interrogating nascent peptide–exit tunnel interaction.